2022
DOI: 10.1109/lgrs.2022.3176616
|View full text |Cite
|
Sign up to set email alerts
|

NASA’s Black Marble Multiangle Nighttime Lights Temporal Composites

Abstract: In addition to the daily Black Marble products (VNP46A1/A2), the recently released temporal composite products (VNP46A3/A4) are generated from daily high-quality, atmospheric, and lunar-Bidirectional Reflectance Distribution Function (BRDF) corrected, Visible Infrared Imaging Radiometer Suite (VIIRS) Day/Night Band (DNB) nighttime radiances (VNP46A2). This letter describes the algorithm of NASA's Black Marble monthly and annual (VNP46A3/A4) Nighttime Light (NTL) composites that are operationally produced for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
(24 reference statements)
0
20
0
Order By: Relevance
“…A related finding is that the production of a VIIRS Black Marble near-nadir output product based on data taken within 20 • of the nadir is a good choice in terms of limiting the variation between observations and also between sites when correcting for nadir angle [18]. Although the resulting mean radiance does not directly enable the true value of emission to be determined, processed data will, at least, be consistent in that the assumption of a Lambertian dependence is closely met over the limited range sampled.…”
Section: Discussionmentioning
confidence: 99%
“…A related finding is that the production of a VIIRS Black Marble near-nadir output product based on data taken within 20 • of the nadir is a good choice in terms of limiting the variation between observations and also between sites when correcting for nadir angle [18]. Although the resulting mean radiance does not directly enable the true value of emission to be determined, processed data will, at least, be consistent in that the assumption of a Lambertian dependence is closely met over the limited range sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, countries close to the Arctic Circle (e.g., United Kingdom, Russia, and Canada) have most of their regions at latitudes with high auroral activity, which causes NTL data to differ significantly from the actual light emission values in these regions. As a result, these aurora-contaminated pixels were filled with gap-filling values [63]. Although the uncertainty in VNP46A4 had not been completely eliminated after the data preprocessing described above, such as the residuary background noise and insensitivity to near-blue wavelengths, the level of impact is slight enough to be competent for subsequent analysis based on numerical statistics.…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…There is a growing body of evidence that there are view angle effects on the brightness of lighting observed from space (Li et al, 2022;Tan et al, 2022;Wang et al, 2022). The view angle effects arise from building and shielding geometries that have yet to be fully explored.…”
Section: Concepts For Future Nighttime Lights Satellite Sensorsmentioning
confidence: 99%
“…Elvidge et al (Elvidge et al, 2020) developed a method for flattening view angel effects in VIIRS DNB temporal profiles and found that there are four main styles of view angle effects: 1) Flat with little-or-no view angle effects, 2) Brighter when viewed from the side, 3) Brighter when viewed at nadir, and 4) Peak-at-nadir. NASA's Black Marble team has begun producing multi-angle cloud-free temporal composites to further explore the information content associated with view angle variations in the brightness of lights observed from space (Wang et al, 2022). Recent studies have pointed out the potential value in having consistently collected variable view angle nighttime lights data collected on urban areas (Kyba et al, 2021).…”
Section: Concepts For Future Nighttime Lights Satellite Sensorsmentioning
confidence: 99%